6(2-3x)=4(5x+7)

Simple and best practice solution for 6(2-3x)=4(5x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2-3x)=4(5x+7) equation:


Simplifying
6(2 + -3x) = 4(5x + 7)
(2 * 6 + -3x * 6) = 4(5x + 7)
(12 + -18x) = 4(5x + 7)

Reorder the terms:
12 + -18x = 4(7 + 5x)
12 + -18x = (7 * 4 + 5x * 4)
12 + -18x = (28 + 20x)

Solving
12 + -18x = 28 + 20x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-20x' to each side of the equation.
12 + -18x + -20x = 28 + 20x + -20x

Combine like terms: -18x + -20x = -38x
12 + -38x = 28 + 20x + -20x

Combine like terms: 20x + -20x = 0
12 + -38x = 28 + 0
12 + -38x = 28

Add '-12' to each side of the equation.
12 + -12 + -38x = 28 + -12

Combine like terms: 12 + -12 = 0
0 + -38x = 28 + -12
-38x = 28 + -12

Combine like terms: 28 + -12 = 16
-38x = 16

Divide each side by '-38'.
x = -0.4210526316

Simplifying
x = -0.4210526316

See similar equations:

| 2(5*555*5)-56= | | 5y+60-9=12+8y-72 | | 200*50+20= | | 9m+5=9m+6 | | m=n-7 | | -34m=12 | | 2x-9y=-3 | | 0=12x+4.9x^2 | | 90-6x=100-8x | | 2(6x-6)+3=2(2x+3)+5 | | 8x-4=10x+19 | | 9xz^2-30xz-96x= | | -2x-7(c+3)=-93 | | 1(a-4)=2(2a+4) | | 8x-4=10+19 | | 4-3yi=4x+16i | | -329=-7(7+5p) | | x=0.5+y | | 3(4x-7)=6-(2-5x) | | 8(-8k-1)=5k-8 | | -11=9-2b | | 31=25-x-x | | 4(2x-7)+4=8 | | 3x+4y-z=4 | | 4x+9=10x+3 | | -59=-4n-3 | | 8-3x+2x=3(x+4) | | 25-7v=10(v-6) | | F(x)=105x | | 10y+5x=30 | | 2c+10=c-2 | | -12x=-228 |

Equations solver categories